1997
DOI: 10.1037/0021-843x.106.1.61
|View full text |Cite
|
Sign up to set email alerts
|

Memory activation and expectancy as prospective predictors of alcohol and marijuana use.

Abstract: This study examined whether indicators of drug-related memory associations predicted drug use prospectively. The predictive effects of outcome expectancies, sensation seeking, and other variables also were investigated. The results revealed that the memory association measures significantly predicted subsequent drug use. Outcome expectancies and sensation seeking predicted alcohol use, but not marijuana use. The findings suggest 2 possibly different aspects of cognition involved in drug use motivation: (a) a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
489
3
10

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 324 publications
(536 citation statements)
references
References 56 publications
34
489
3
10
Order By: Relevance
“…They defined implicit cognitions as "the introspectively unidentified (or inaccurately identified) trace of past experience that mediates a response" (p. 5). In addition, the use of implicit as well as explicit measures may be of importance because they could tap different underlying cognitive-motivational processes (Stacy, 1997;Wilson et al, 2000). 1 Several approaches have been taken to assess alcohol-related cognitions in more implicit ways.…”
Section: Implicit Alcohol-related Cognitionsmentioning
confidence: 99%
See 2 more Smart Citations
“…They defined implicit cognitions as "the introspectively unidentified (or inaccurately identified) trace of past experience that mediates a response" (p. 5). In addition, the use of implicit as well as explicit measures may be of importance because they could tap different underlying cognitive-motivational processes (Stacy, 1997;Wilson et al, 2000). 1 Several approaches have been taken to assess alcohol-related cognitions in more implicit ways.…”
Section: Implicit Alcohol-related Cognitionsmentioning
confidence: 99%
“…Another explanation could be that people have a dual attitude toward alcohol (Wilson et al, 2000). The finding that explicit and implicit cognitions uniquely contribute to the variance explained in prospective alcohol use could be interpreted as support for separate implicit and explicit processes that influence drug-related decision making (Stacy, 1997; but see Footnote 1).…”
Section: Implicit and Explicit Cognitive-motivational Constructsmentioning
confidence: 99%
See 1 more Smart Citation
“…알코올기대이론(alcohol expectancy theory; Leigh, 1989)은 알코올이 자신에게 미칠 행동, 기 분, 정서에 대한 기대가 알코올 사용과 관련된 행동에 직·간 접적으로 영향을 준다고 설명한다. 알코올기대는 알코올이 사람에게 미칠 영향에 대한 믿음 (Leigh, 1989), 알코올결과 에 대해 주관적으로 평정하는 가능성 (Stacy, 1997)이라고 정의를 내린다. 알코올기대는 음주행동을 일으키는 요인일 뿐만 아니라 알코올중독의 인지적 위험요인이다 (Goldman, 1994 …”
unclassified
“…Consistent with this view, Rather et al (1992) reported that in a 'map' of the relations between alcohol-related concepts and other information for heavy and light drinkers, conceptual organization was more centered around the alcohol concepts for heavy drinkers compared to light drinkers (cf. Stacy, 1997). Tiffany's (1990) proposal does not involve information about emotional salience, and so it can be examined with emotionally neutral stimuli.…”
Section: Introductionmentioning
confidence: 99%